Great minds of the western intellectual tradition. Part 6 modernism and the age of analysis. - Staloff, Darren 1961-.; Markos, Louis; Dalton, Dennis G.; Solomon, Robert C.; Risjord, Mark W. 1960-.; Kellner, Douglas 1943-.; Burgstaller, Andreas; Teaching Company Limited Partnership (Chantilly, Va. Teaching Co., 2000)
Lectures based on the seminar course at Columbia University on Western intellectual history augmented by additional lectures by selected "guest" lecturers. Gives a guided tour through 3,000 years of Western thought.
disc 11. lecture 61. Introduction / Darren M. Staloff ; lecture 62. James' pragmatism / Darren M. Staloff ; lecture 63. Freud's psychology / Dennis G. Dalton ; lecture 64. Freud's discontents / Dennis G. Dalton ; lecture 65. A.J. Ayer and logical positivism / Darren M. Staloff ; lexture 66. Max Weber and legitimate authority / Darren M. Staloff -- disc 12. lecture 67. Husserl and phenomenology / Robert C. Solomon ; lecture 68. Dewey's critique of traditional philosophy / Darren M. Staloff ; lecture 69. Heidegger - Dasein and Existenz / Robert C. Solomon ; lecture 70. Wittsgenstein and language analysis / Mark W. Risjord ; lecture 71. The Frankfurt School / Douglas Kellner ; lecture 72. Structuralism - Saussure and Levi-Strauss / Louis Markos.
Title from container.
Continues disc 9 and disc 10 of part 5.
DVD.
Keywords: Philosophy -- History; Civilization, Western -- Philosophy